Home » Simplify (frac{4frac{3}{4} – 6frac{1}{4}}{4frac{1}{5} text{ of } 1frac{1}{4}})

Simplify (frac{4frac{3}{4} – 6frac{1}{4}}{4frac{1}{5} text{ of } 1frac{1}{4}})

Simplify (frac{4frac{3}{4} – 6frac{1}{4}}{4frac{1}{5} text{ of } 1frac{1}{4}})

  • A.
    -7(frac{7}{8})
  • B.
    (frac{-2}{7})
  • C.
    (frac{-10}{21})
  • D.
    (frac{10}{21})
Correct Answer: Option B
Explanation

(frac{4frac{3}{4} – 6frac{1}{4}}{4frac{1}{5} text{ of } 1frac{1}{4}})
(frac{19}{4}) – (frac{25}{4})…………(A)
(frac{21}{5}) x (frac{5}{4})………….(B)
Now work out the value of A and the value of B and then find the value (frac{A}{B})
A = (frac{19}{4}) – (frac{25}{4})
= (frac{-6}{4})
B = (frac{21}{5}) x (frac{5}{4})
= (frac{105}{20})
= (frac{21}{4})
But then (frac{A}{B}) = (frac{-6}{4}) (div) (frac{21}{4})
= (frac{-6}{4}) x (frac{4}{21})
= (frac{-24}{84})
= (frac{-2}{7})

Related:  Rationalize the expression (frac{1}{sqrt{2} + sqrt{5}})